2010
DOI: 10.1375/twin.13.1.79
|View full text |Cite
|
Sign up to set email alerts
|

A Twin-Singleton Comparison of Developmental Trajectories of Externalizing and Internalizing Problems in 6- to 12-Year-Old Children

Abstract: R esearch on twin-singleton differences in externalizing and internalizing problems in childhood is largely cross-sectional and yields contrasting results. The goal of this study was to compare developmental trajectories of externalizing and internalizing problems in 6-to 12-year-old twins and singletons. Child Behavior Checklist (CBCL) maternal reports of externalizing and internalizing problems were obtained for a sample of 9651 twins from the Netherlands Twin Register and for a representative general popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
48
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(60 citation statements)
references
References 41 publications
8
48
0
4
Order By: Relevance
“…A diminuição encontrada tem amplo respaldo na literatura (Bolsoni-Silva et al, 2010;Miner & Clarke-Stewart, 2008;Robbers et al, 2010) e corresponde a uma tendência de desenvolvimento, relacionada ao aumento da auto-regulação (Bee, 2003;Skinner & Zimmer-Gembeck, 2007). O resultado se repetiu no grupo dos meninos, especifi camente entre o 3º e o 5º ano.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…A diminuição encontrada tem amplo respaldo na literatura (Bolsoni-Silva et al, 2010;Miner & Clarke-Stewart, 2008;Robbers et al, 2010) e corresponde a uma tendência de desenvolvimento, relacionada ao aumento da auto-regulação (Bee, 2003;Skinner & Zimmer-Gembeck, 2007). O resultado se repetiu no grupo dos meninos, especifi camente entre o 3º e o 5º ano.…”
Section: Discussionunclassified
“…Estudos longitudinais com foco em trajetórias de desenvolvimento demonstram redução dos comportamentos externalizantes no EF (Bolsoni-Silva et al, 2010;Miner & Clarke-Stewart, 2008;Robbers et al, 2010). Para comportamentos internalizantes, a evidência disponível é mais restrita.…”
Section: Trajetórias De Desenvolvimento Psicossocial Nos Anos Do Ensiunclassified
“…Consequently, birth weight may have somewhat different meaning in twins than in singletons, and thus replication in an adoptive sample may provide similar genetically-informative findings without the limited generalizability. On a positive note, although physical growth in twin samples shows large deviation from singleton norms, a recent investigation found that the trajectories of externalizing symptoms across twins and singletons during middle and late childhood were very similar (Robbers et al, 2010). These findings suggest that research on the development of externalizing psychopathology in twins may be generalizable to nontwin populations.…”
Section: Discussionmentioning
confidence: 99%
“…Twins (n = 173) were excluded, given previous literature suggesting that the sibling relationship between twins may be distinct from that of singletons. 25,26 Outcome data were available for 3452 adolescents at 18 years. A sample with complete data across all exposure, outcome, and confounding variables (n = 2002) was used to investigate the main and adjusted association between sibling bullying and depression at 18.…”
Section: Data Sourcementioning
confidence: 99%